ADAPTATION OF POLYMERASE CHAIN REACTION-RESTRICTION FRAGMENT LENGTH POLYMORPHISM METHOD FOR POLYMORPHISM (RS2583988) ANALYSIS IN ALPHA-SYNUCLEIN GENE - Tarianyk, K.A.; Lytvynenko, N.V.; Oliinychenko, V.K.; Byslik, T.V.; Pochernyaev, K.F. (World of Medicine and Biology, 2020)
The article suggests the polymerase chain reaction-restriction fragment length polymorphism method for a single nucleotide polymorphism (rs2583988) detection for further prediction of Parkinson’s disease risks. Based on the meta-analysis results for the single nucleotide polymorphism rs2583988 (C>T) in αlpha-synuclein gene; current polymorphic variant was chosen by analyzing bioinformatical and genetic studies. We have designed a pair of primers and conditions for restriction analysis to detect different alleles in rs2583988. As a result, there was developed a simple and affordable method for detecting single nucleotide polymorphism rs2583988 alleles. The method is expected to be suitable for clinic laboratories, due to affordable cost and equipment, and to be used in further association studies.